(untitled) (American International Journal of Agricultural Studies, 2023)
Rice is a major staple crop in Bangladesh, and its production has a profound effect on the country’s agricultural sector. Large distribution networks in Bangladesh may drive up rice prices. The scarcity of marketing information prevents farmers from making decisions when planning their output and sales. This study aimed to analyze the variables that influence mobile usage and the effects of mobile use in rice marketing. 100 farmers were selected by two steps sampling procedure from the rural area of Upazilla, Bangladesh. 100 farmers in all, mostly small-scale rice farmers with an average plot size of 1.88 acres, were approached using a concise interview format & questionnaires. The data was evaluated using a variety of statistical methods, including correlation and regression analysis using a binary logistic regression model. The analysis was carried out utilizing the SPSS. Studies showed that 75% of mobile phone owners utilize it for paddy marketing. Income and education have a significant influence on cellphone usage, as shown in regression analysis. In the Likert scale study, there was a highly positive impact on having access to a broad variety of information, the accuracy of that information, negotiating power, and reducing market intermediaries’ and transportation corporations’ oppressiveness. Most farmers can save time and money by acquiring information themselves. It can be concluded that the adoption of mobile phones facilitates marketing activities and all potential consequences for rice farmers. Assuring mobile phone utilization could be essential in this area to improve the calibre of rice marketing. JEL Classification Codes: O13, O33, Q11, Q13.